RE-TESTING AND SEROCONVERSION AMONG HIV TESTING AND COUNSELING CLIENTS IN LESOTHO - Grabbe, Kristina L. (AIDS Educ Prev, 2015)
HIV testing and counseling (HTC) is an essential component of comprehensive HIV programs. Retrospective HTC program data from 2006 to 2010 were examined to determine patterns of re-testing and seroconversion in Lesotho. Among 104,662 initially negative clients, 6,777 (6.5%) were re-testers. Predictors of re-testing included being male, age ≥ 25 years, divorced/separated, having more than a high school education, being tested as a couple, testing in the year 2006, testing in the capital city, and awareness of partner’s recent testing behavior. Among re-testers who seroconverted (N = 259), predictors included being female and having less than a high school education. There is a critical need for more effectively targeting HIV retesting messages to align with WHO (2010) guidelines and identify persons at highest risk for HIV, to increase timely diagnoses and link persons to appropriate HIV prevention, care, and treatment services.